Answer:
x = -14
Steps:
Rewrite the equation as -8 = 6+x
Then move all terms not containing x to the right side of the equation.
x = -8-6
Afterwords subtrack.
x = -14.
hope this helps :)
To solve for 'f' in the algebraic equation 's=3f-24', add 24 to 's' and then divide the result by 3.
To solve the algebraic equation 's=3f-24' for 'f', you would first decide to isolate 'f'. To do this, start by getting rid of the '-24' on the right side of the equation by adding 24 to both sides. This would simplify the equation to 's+24=3f'. Next, divide both sides of the equation by 3. This step will result in a final solution of 'f=(s+24)/3'. So, to solve for 'f' in the provided equation, simply add 24 to the original 's' value and then divide the result by 3.
#SPJ2
Keywords:
average rate of change, parabola, interval, points
For this case we have to find the average rate of change of a parabola in the interval from to . To do this, we need two points for the parabola pass, and apply the following formula:
We have the following points, taking into account that:
Substituting:
So, the average rate of change for the given graph is 0 in the given interval
Answer:
Answer:
Average rate of change(A(x)) of f(x) over the interval [a, b] is given by:
As per the statement:
From the given graph as shown :
At x = -2
then;
f(-2) = -1
At x = 0
then;
f(0) = -1
To find the average rate of change for the given graph from x = –2 to x = 0 .
Substitute the given values we have;
⇒
⇒
⇒
Therefore, the average rate of change for the given graph from x = –2 to x = 0 is, 0